THE METHOD OF COUNTERACTING RADICALISM IN SCHOOLS: Tracing the Role of Islamic Religious Education Teachers in Learning - Tambak, Syahraini (State Islamic University North Sumatra, 2021)
Abstract: The Researches of radicalism have been widely studied, but the methods to counteract in school have not yet been found. This study aims to explore the methods of Islamic religious education teachers in counteracting radical understanding of students in learning. This research used a case study approach that was carried out for two years in high school in Pekanbaru which conducting interviews with teachers, principals, and students. This research produced a method which the teacher counteracts radicalism in learning are dissemination of understanding and the dangers of radicalism. The examples of them are tolerance and living in harmony, oversee Islamic spiritual activities, companion to religious activities, instilling moderate Islamic teachings, transmitter of Islâm kâffah teachings and dialogue about similarity in learning. The implication of this research is to develop the theory of “The methods to counter radicalism in schools” in education, by strengthening the methods used by teachers in countering radicalism in learning. Keywords: radicalism, Islamic religious teacher, teaching method, learning